AN ANALYSIS OF STUDENTS’ ERROR IN USING PERSONAL PRONOUN AS SUBJECT AND OBJECT - Insan Abadi Mulyo; Marnina Marnina (Universitas Musamus Merauke, 2019)
The objectives of this research are to find students' error in using personal pronouns as subject and object which made by seventh grade students of SMP Negeri 6 Merauke. The subject in this research was the students of SMP Negeri 6 Merauke grade VII A that consists of 35 students that was selected by using purposive sampling. This research was used descriptive qualitative method. The data were collected from the test. The type of test was essay test that given twice to students. Data from the test results were used to find out students' errors. First, student errors were classified using Corder theory that consists of four kinds of error; those are omission, addition, selection, and ordering. After that, the errors were analyzed by calculating the frequency of each type of error and then calculating the percentage to know what the types of error that are most often done by students. From the results of this study, has been obtained the total error of students are 429 errors. The most error are selection errors with 385 errors (89.74%), and then ordering errors with 38 errors (8.86%), and then omission errors with 3 errors (0.70%) and error addition also has the same total that is 3 errors (0.70%). Therefore, the most error that made by students of grade VII A of SMP Negeri 6 Merauke is selection error. Keywords: personal pronoun; student’s error; grammar